Cathodic biofilms – A prerequisite for microbial electrosynthesis. (March 2022) - Vassilev, Igor; Dessì, Paolo; Puig, Sebastià; Kokko, Marika
Graphical abstract: Highlights: Resilient and robust biofilms are required for microbial electrosynthesis. Biocompatible materials reinforce microbial adherence and growth. Substrate and nutrient availabilities could limit biofilm development. Counter reaction plays a role in the evolution of cathodic electro-active biofilms. Long-term studies are required to understand their effects on cathodic biofilms. Abstract: Cathodic biofilms have an important role in CO2 bio-reduction to carboxylic acids and biofuels in microbial electrosynthesis (MES) cells. However, robust and resilient electroactive biofilms for an efficient CO2 conversion are difficult to achieve. In this review, the fundamentals of cathodic biofilm formation, including energy conservation, electron transfer and development of catalytic biofilms, are presented. In addition, strategies for improving cathodic biofilm formation, such as the selection of electrode and carrier materials, cell design and operational conditions, are described. The knowledge gaps are individuated, and possible solutions are proposed to achieve stable and productive biofilms in MES cathodes.